Seismic demand on column splices in concentrically braced frames considering brace fracture. (December 2020) - Faytarouni, Mahmoud; Shen, Jay; Seker, Onur; Akbas, Bulent
Abstract: An evaluation of the seismic demands on column splices in special concentrically braced frames (SCBFs) at different system response levels is presented. Because of the critical nature of column splices and the absence of inclusive research that quantify seismically induced demands with respect to design requirements, this paper aims to investigate the level of splice demands in ductile CBFs. The study assesses the nonlinear dynamic response of 5- and 13-story SCBFs with the common two-story X-bracing configuration under an ensemble of earthquake ground motion records. The study concludes that when the likelihood of brace fracture is high, the required design strength for column splices under tensile and shear force demands yield a high margin of safety. On the other hand, as the likelihood of brace fracture increases, the flexural and the combined axial force and flexural demands become significant. Column splices seem to withstand flexural demands larger than the required by the current design code. Furthermore, column splices under the combined axial and flexural demands appear to attain the capacity of the smaller column, particularly when brace fracture becomes inevitable Graphical abstract: Unlabelled Image Highlights: Evaluation of seismic design provisions for column splices in braced frames. High level of protection against safety for splices under tensile and shear demands. Flexural demands exceed the minimum prescribed in the current design practice. Low level of protection against safety for splices under combined demands.